(3QSGdI aj ChbGa GdcaQs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; gPg ChbGa GdcaQ GYde Cf aj GdbQBf SHYI YTQ ehVYG dG jLhR Gdhba YdjgG Gf cGf YGdeG YGeOG hhba Ydi gPg GdehGVY aEfg jcaQ ShGA cGf aj GdUdGI Ch NGQL GdUdGI HGdELeGYs
(3BNQgG (B:s
(3GdSGHY YTQ Cf jba Ydi bhdg Ef GdEfSGf daj NSQ Ke jHJOF Hbhdg EdG GdPjf BefhGs
(3JHUQI GdYfhGf (B:s
(3gPg GdQSGdI efbhdg ef aJGhi GdedJbWs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdbQGAGJ hGdJLhjOs